2021
DOI: 10.1111/1751-2980.12969
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of bile acid diarrhea in patients with chronic diarrhea

Abstract: ObjectiveBile acid diarrhea is a form of chronic diarrhea caused by excessive bile reaching the colon. Conditions involving the terminal ileum and cholecystectomy are predisposing factors but an idiopathic form of bile acid diarrhea has also been described. In this study we aimed to evaluate the prevalence of bile acid diarrhea in patients consecutively evaluated for chronic diarrhea in an Outpatient Gastroenterology Clinic.MethodsMedical records of all patients admitted for chronic diarrhea (>4 weeks) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…99 A trial of therapy with colestyramine was suggestive for bile acid diarrhoea in 28% of patients with chronic diarrhoea. 100 We concur with consensus guidelines developed independently, which recommend testing to exclude bile acid diarrhoea, with SeH-CAT or other biomarkers, as available, in all patients with unexplained chronic diarrhoea. Summary of evidence: SIBO is defined by excessive and/or an abnormal type of bacteria in the small bowel.…”
Section: Summary Of Evidencesupporting
confidence: 68%
See 1 more Smart Citation
“…99 A trial of therapy with colestyramine was suggestive for bile acid diarrhoea in 28% of patients with chronic diarrhoea. 100 We concur with consensus guidelines developed independently, which recommend testing to exclude bile acid diarrhoea, with SeH-CAT or other biomarkers, as available, in all patients with unexplained chronic diarrhoea. Summary of evidence: SIBO is defined by excessive and/or an abnormal type of bacteria in the small bowel.…”
Section: Summary Of Evidencesupporting
confidence: 68%
“…In patients with Rome IV criteria for IBS‐D, bile acid diarrhoea was the most common organic disease diagnosed 99 . A trial of therapy with colestyramine was suggestive for bile acid diarrhoea in 28% of patients with chronic diarrhoea 100 …”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16] Bile acid malabsorption is well described in the literature regarding resection of terminal ileum. Alterations in bile acid absorption may be associated with both functional and organic types of chronic diarrhoea, [17][18][19] and the variation we found in the length of terminal ileum specimens could theoretically give various clinical types of chronic diarrhoea due to alterations in bile acid absorption. 18 A study found that the severity of diarrhoea, expressed as faecal weight, corresponded to the length of removed ileum and colon, 20 and this emphasizes the importance of the length of the specimens.…”
Section: Discussionmentioning
confidence: 76%
“…Alterations in bile acid absorption may be associated with both functional and organic types of chronic diarrhoea, [17][18][19] and the variation we found in the length of terminal ileum specimens could theoretically give various clinical types of chronic diarrhoea due to alterations in bile acid absorption. 18 A study found that the severity of diarrhoea, expressed as faecal weight, corresponded to the length of removed ileum and colon, 20 and this emphasizes the importance of the length of the specimens. Another study found no correlation between B12 malabsorption and < 20 cm of resected terminal ileum, 21 and with an upper limit of terminal ileum specimen length of 17 cm in this study, we do not know if it is of relevance in the general population of patients after standard right hemicolectomy.…”
Section: Discussionmentioning
confidence: 76%
“…The BASs are also proven to be efficacious in the treatment of chronic diarrhea due to the malabsorption of BAs/BSs, often termed as bile acid diarrhea (BAD). Studies had shown that patients with post-ileocecal resection experience a reduction in stool frequency and had an improvement in consistency of stool on a specific dose of cholestyramine per day; additionally, the urgency of defecation, perianal soreness, and flatus were also decreased in most cases. In patients with mild diarrhea, bile acid sequestrants provide symptomatic relief by lowering the concentration of free bile acids in the colon. , Figure represents the list of off label use of BASs reported in various literature and research guidelines.…”
Section: Polymeric Bass In the Market: Mechanism Indications Advantag...mentioning
confidence: 99%